The role of the Amazon Basin moisture in the atmospheric branch of the hydrological cycle: a Lagrangian analysis - A. Drumond; J. Marengo; T. Ambrizzi; R. Nieto; L. Moreira; L. Gimeno (Hydrology and Earth System Sciences, 2014)
We used a Lagrangian model (FLEXPART) together with the 1979–2012 ERA-Interim reanalysis data to investigate the role of the moisture in the Amazon Basin in the regional hydrological budget over the course of the year. FLEXPART computes budgets of evaporation minus precipitation by calculating changes in the specific humidity along forward and backward trajectories. The tropical Atlantic is the most important remote moisture source for the Amazon Basin. The tropical North Atlantic (NA) mainly contributed during the austral summer, while the contribution of the tropical South Atlantic (SA) prevailed for the remainder of the year. At the same time, the moisture contribution from the Amazon Basin itself is mainly for moisture supplying the southeastern South America. The 33-year temporal domain allowed the investigation of some aspects of the interannual variability of the moisture transport over the basin, such as the role of the El Niño Southern Oscillation (ENSO) and the Atlantic Meridional Mode (AMM) on the hydrological budget. During the peak of the Amazonian rainy season (from February to May, FMAM) the AMM is associated more with the interannual variations in the contribution from the tropical Atlantic sources, while the transport from the basin towards the subtropics responds more to the ENSO variability. The moisture contribution prevailed from the SA (NA) region in the years dominated by El Niño/positive AMM (La Niña/negative AMM) conditions. The transport from the Amazon towards the subtropics increased (reduced) during El Niño (La Niña) years.